Difficulties and Misconceptions of Students in Learning Limit - Adhikari, Krishna Prasad (Interdisciplinary Research in Education, 2021)
The purpose of this study is to explore the difficulties and misconceptions of secondary level students in learning limit of the function. In this study, which used mix-method design, regarding difficulties and misconceptions, a concept test was used on 200 grade XII students of Kathmandu Metropolitan City of Nepal, and interviews were conducted on 12 purposively selected students from 200 students. The data obtained from the test was categorized as the category of the responses and interpreted using a percentage score. In addition to that, the data obtained from the interview was analyzed and interpreted by using a general qualitative approach. The finding of the study revealed that student’s difficulties in solving a limit problem have aroused because of the lack of conceptual clarity on the limit of the function. Similarly, the student has misconception on indeterminate and infinite, limiting and functional value of the function, and symbolic representation of infinity.